Fabrication of TiO2 Nanofilm Photoelectrodes on Ti Foil by Ti Ion Implantation and Subsequent Annealing - Yichao Liu; Feng Ren; Guangxu Cai; Mengqing Hong; Wenqing Li; Xiangheng Xiao; Wei Wu; Changzhong Jiang (Advances in Condensed Matter Physics)
The TiO2 photoelectrodes fabricated on the substrate of Ti foils by Ti ions implantation and subsequent annealing at different temperatures were applied for water splitting. The size of TiO2 nanoparticles increased with annealing temperatures, and the GIXRD patterns and Raman spectra demonstrate that the phase of TiO2 turns to rutile at high temperature. The photoelectrochemical (PEC) and X-ray photoelectron spectroscopy (XPS) spectra of the valence band demonstrate that the samples annealed at 400 and 500°C show the n-type property. The sample annealed at 600°C shows the weak p-type TiO2 property. For the sample annealed at 700°C, the negative photocurrent is main, which mainly performs the p-type property of TiO2. The IPCE values indicate that the absorption edges are red shifted with the increase of annealing temperatures.